Quality assurance program on stereotactic radiosurgery: report from a Quality Assurance Task Group - Hartmann, Günther H. (Springer Berlin Heidelberg, 1995)
Radiosurgery performed with the "Gamma Knife" or on a linac facility is a specific radiotherapy method to treat certain lesions in the brain with a high single radiation dose. Geometric miss of a radiosurgica target is considered the most likely serious error in a stereotactic radiosurgery treaatment. Therefore, the issue of quality assurance in stereotactic radiosurgery is a serious one for neurosurgeons, physicists, patients and those of us who wish to analyze the results of radiosurgery. The purpose of this book is to offer and describe a quality assurance program and procedures of the physical and technical aspects through identifying the sources of possible errors and suggesting quality assurance tests that should be performed in order for a stereotactic system to be used clinically
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 2012